2007
DOI: 10.1227/01.neu.0000290892.46954.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tobacco Dose and Length of Exposure on Delayed Neurological Deterioration and Overall Clinical Outcome After Aneurysmal Subarachnoid Hemorrhage

Abstract: The duration and timing of tobacco use, rather than the dose of tobacco per se, seem to be risk factors for delayed neurological deterioration after aneurysmal SAH. Although we did not find an association between tobacco use and overall clinical outcome after aneurysmal SAH, these results suggest that the distribution of various patterns of tobacco use within a given data set may influence the overall results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Thirty-three studies (63%) were rated as HQ. [9][10][11][12][13]15,16,[18][19][20]22,[28][29][30][31]35,36,38,39,[41][42][43]46,[48][49][50][51][52][53][54][55][56][57] Appendix 1 summarizes the study characteristics and the investigated variables. Altogether, 33 variables were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three studies (63%) were rated as HQ. [9][10][11][12][13]15,16,[18][19][20]22,[28][29][30][31]35,36,38,39,[41][42][43]46,[48][49][50][51][52][53][54][55][56][57] Appendix 1 summarizes the study characteristics and the investigated variables. Altogether, 33 variables were reported.…”
Section: Resultsmentioning
confidence: 99%
“…28 Case fatality remained fairly stable over time in this study, whereas others have suggested a decline over the past few decades. 7,29 Previous studies have found a higher risk of vasospasm and delayed ischemic neurologic deficit after aSAH among smokers, 30,31 and it has been suggested that immediate vasospasm may reduce the severity of the initial hemorrhage. Of these excluded patients, more were older than 70 years of age and died within 2 weeks during the 2 first time periods (1984 -1994) compared with after 1995.…”
Section: Resultsmentioning
confidence: 99%
“…For example, despite the fact that there were no differences in initial severity of illness (as measured by Hunt and Hess grade) between study groups, there was a significant reduction in the proportion of patients who were smokers between the two study groups (36.8% to 26.2%). Though smoking has been associated with the development of delayed ischemic deficits, it has not been shown to impact overall outcome following aneurysmal SAH [20]. In order to test the sensitivity of smoking and other risk factors on the finding in this study, it was re-estimated both univariate and multivariate regression models including only the risk factors (individually and as a group).…”
Section: Discussionmentioning
confidence: 99%